2019
DOI: 10.1007/s40744-019-0159-1
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Arthritis: What is Happening at the Joint?

Abstract: Psoriatic arthritis (PsA) is a heterogeneous and inflammatory disease with diverse clinical manifestations, including psoriasis, nail psoriasis, peripheral joint disease, axial joint disease, enthesitis, and dactylitis. Typically, this varied clinical presentation complicates the clinician’s ability to distinguish PsA from other forms of arthritis. In the synovium of individuals with PsA, upregulation of the genes WNT3A , BMPR2 , and TGFBR1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 80 publications
1
40
0
5
Order By: Relevance
“…The bioinformatic functional analysis revealed that COL10A1 plays a role in maintaining bone homeostasis and cartilage metabolism as well as in the organization and remodeling of ECM. This result supports the potential implication of bone and cartilage metabolism-related processes in the onset and progression of PsA [20]. Accordingly, it has been found that Collagen X metabolism was enhanced in patients affected by PsA and Axial Spondyloarthritis [21].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The bioinformatic functional analysis revealed that COL10A1 plays a role in maintaining bone homeostasis and cartilage metabolism as well as in the organization and remodeling of ECM. This result supports the potential implication of bone and cartilage metabolism-related processes in the onset and progression of PsA [20]. Accordingly, it has been found that Collagen X metabolism was enhanced in patients affected by PsA and Axial Spondyloarthritis [21].…”
Section: Discussionsupporting
confidence: 81%
“…Of note, it is known that psoriatic patients may experience an aberrant vascularization of the dermis towards the epidermis, due to an overexpression of proangiogenic factors induced by the alteration of cell proliferation pathways. These vessels are characterized by tortuous capillary loops, which may contribute to exacerbate the disease symptoms in patients affected by Ps and PsA [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…[84] Since angiogenesis and VEGF-A also play a key role in the pathogenesis of psoriatic arthritis, patients with this phenotype may profit from a systemic therapy that targets the vasculature. [85,86] A case report of remission of psoriatic arthritis following bevacizumab therapy [78] supports the concept that anti-VEGF-A therapy may be a potential treatment option for both the skin and joint manifestations of psoriasis.…”
Section: Veg F-a Inhib Iti On a S A Novel S Tr Ategy For The Manag mentioning
confidence: 92%
“…PsA affects people heterogeneously with a range of clinical manifestations, like inflammatory arthritis, dactylitis, enthesitis, spondylitis, skin psoriasis and nail disease. The disease has a significant impact on patients' physical function, social participation, and quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%